(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
In today’s higher education institutions, mental health issues among university students have become a major worldwide concern. Anxiety, despair, and psychological distress are becoming more common among students due to increased academic pressure, unstable finances, social isolation, and unclear employment prospects. Universities serve as places that foster students’ intellectual, emotional, and moral growth in addition to being centres for the spread of knowledge. As a result, safeguarding students’ mental health has grown to be a significant institutional and societal obligation. By combining viewpoints from law, psychology, ethics, and education policy, this multidisciplinary study investigates the moral dilemmas and mental health difficulties encountered by college students. The study examines the ways in which social injustices, digital technology, academic competition, and institutional settings affect students’ psychological health. Critical analysis is done on ethical issues such academic integrity, institutional responsibility, privacy violations, harassment, and discrimination. The study also assesses the legal and policy frameworks that control student wellbeing in universities, including rules pertaining to access to mental health support services, equality, and dignity. Additionally, the study investigates how colleges might support mental health advocacy through inclusive institutional policies, awareness campaigns, and counselling services. It draws attention to the significance of moral leadership in educational establishments and stresses the necessity of all-encompassing support networks that deal with the structural and psychological elements influencing student’swellbeing. The study comes to the conclusion that multidisciplinary cooperation between educators, psychologists, legal experts, and legislators is necessary to address mental health issues among college students. Universities need to take proactive measures that incorporate legal protections, ethical responsibility, and mental health awareness. These programs are crucial for creating secure, welcoming, and encouraging learning environments that support student’s general development and increase the efficacy of higher education systems as a whole.